The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/1479164115597867
|View full text |Cite
|
Sign up to set email alerts
|

Prior treatment with dipeptidyl peptidase 4 inhibitors is associated with better functional outcome and lower in-hospital mortality in patients with type 2 diabetes mellitus admitted with acute ischaemic stroke

Abstract: It is unclear whether prior antidiabetic treatment affects stroke severity and outcome. To evaluate this association, we prospectively studied all patients who were admitted in our Department with acute ischaemic stroke (n = 378, mean age = 78.8 ± 6.5 years). The severity of stroke was assessed at admission with the National Institutes of Health Stroke Scale. The outcome was assessed with the modified Rankin Scale at discharge and with in-hospital mortality. A total of 123 patients had type 2 diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…A recent prospective human study has shown that prior treatment with gliptins is associated with better functional outcome and lower mortality in stroke patients with T2D . This observation is supported by recent preclinical results that have shown a strong neuroprotective action of the gliptin linagliptin in normal mice and mice with T2D, where chronic DPP‐4 inhibition before (4 weeks) and after (3 weeks) experimental stroke reduced brain damage .…”
Section: Introductionmentioning
confidence: 66%
“…A recent prospective human study has shown that prior treatment with gliptins is associated with better functional outcome and lower mortality in stroke patients with T2D . This observation is supported by recent preclinical results that have shown a strong neuroprotective action of the gliptin linagliptin in normal mice and mice with T2D, where chronic DPP‐4 inhibition before (4 weeks) and after (3 weeks) experimental stroke reduced brain damage .…”
Section: Introductionmentioning
confidence: 66%
“…Despite these promising results of preclinical studies, there are very few data regarding the role of DPP-4 inhibitors in improving the outcome of patients with acute ischemic stroke. In a small study ( n = 123), we reported that patients who were hospitalized with acute ischemic stroke and were treated with DPP-4 inhibitors prior to stroke had a trend for less severe stroke at admission and also had better functional outcome and lower in-hospital mortality than patients treated with other antihyperglycemic agents [ 50 ].…”
Section: Dpp-4 Inhibitors and Acute Ischemic Strokementioning
confidence: 99%
“…Rat models showed that PEDF induces the production of inflammatory chemokines such as MIP-2 and MIP-3 α in microglia [136]. The myokine dipeptidyl-peptidase 4 (DPP4) has recently come in the spotlight because its inhibition, as well as the use of glucagon-like receptor 1 (GLP-1) agonists, leads to an antistroke effect [137, 138] and a cardioprotective role [139]. During physical exercise, DPP4 inhibitors improve mitochondrial biogenesis and muscle activity through the activation of GLP-1 signaling [140].…”
Section: Bone-skeletal Muscle Biomarkers In Strokementioning
confidence: 99%